Errors and difficulties in oral reading in Pilipino of grade two pupils in six elementary schools, Districts of Talisay, Division of Batangas - Landicho, Leovigildo B. 1919- (1969)
The purpose of the study is to make a critical analysis of the oral reading errors and difficulties in Pilipino of Grade Two pupils. At the same time, this is a pilot research in the field of oral reading in Pilipino which is the medium of instruction in Grades I and II. It aims to know the exact nature of the oral reading errors and difficulties in Pilipino and to suggest ways and means to correct them.